The Influence of Live Streaming, Flash Sale, and Online Customer Review on Purchasing Decisions for Antarestar Products on TikTok Shop - Rofiq Ainul Husin; Subagyo, Subagyo (Universitas Nusantara PGRI Kediri, 2025)
Research aim : Aiming to understand and analyze how live streaming, flash sale, and online customer review, both partially and simultaneously, influence customers decisions to purchase Antarestar products on TikTok Shop. Design/Methode/Approach : A causal quantitative approach is applied in this research. The research population includes TikTok Shop users who have previously purchased Antarestar products. The sample used consisted of 40 samples selected through purposive sampling based on the criteria: (1) having a TikTok Shop account and (2) having purchased Antarestar products at least once. Primary data were obtained through a Likert scale-based questionnaire, and multiple linear regression was used for data analysis. Research Finding : This research indicates that flash sale have a significant impact on customers' decisions to purchase Antarestar products on TikTok Shop, while live streaming and online customer review do not have a significant impact. Theoretical contribution/Originality : Useful as a reference for subsequent studies examining the influence of live streaming, flash sale, and online customer review on customer purchase decisions on e-commerce platforms, particularly TikTok Shop. Practitionel/Policy implication : This research is expected to help Antarestar formulate a more optimal marketing approach on TikTok Shop by leveraging the influence of live streaming, flash sale, and online customer review to enhance customers' purchasing decisions. Research limitation : The research focuses on examining customer decisions to purchase Antarestar products on TikTok Shop, with live streaming features, flash sale, and online customer review serving as independent variables, while purchase decisions serve as the dependent variable.